Earth politics : religion, decolonization, and Bolivia's indigenous intellectuals - Ari Chachaki, Waskar (Narrating native histories., 2014)
Earth Politics focuses on the lives of four indigenous activist-intellectuals in Bolivia, key leaders in the Alcaldes Mayores Particulares (AMP), a movement established to claim rights for indigenous education and reclaim indigenous lands from hacienda owners. The AMP leaders invented a discourse of decolonization, rooted in part in native religion, and used it to counter structures of internal colonialism, including the existing racial systems. Waskar Ari calls their social movement, practices, and discourse ""Earth Politics, "" both because of the political meaning that the